Vibration power flow analysis of laminated composite structures - Zhu, Chendi (2021)
Laminated composite structures have been increasingly used in engineering structures due to the beneficial properties such as light weight, high stiffness-to-weight ratio, high strength-to-weight ratio and design flexibility. Understanding the vibration behaviour of composite structures is of vital importance to achieve optimal structural design with excellent dynamic performance in terms of low vibration and noise level. However, because of the complexity in modelling and simulation, the vibration energy flow behaviour of laminated composite structure remains largely unexplored and needs detailed investigations. The vibration power flow analysis (PFA) approach is a widely accepted technique to characterize the dynamic behaviour of complex structures. It has been extensively used for vibration analysis of metallic structures, but not of composite materials. This thesis aims to develop effective vibration power flow analysis methods for laminated composite structures to reveal its dynamic behaviour and vibration energy transmission characteristics.